2018
DOI: 10.1038/s41598-018-25780-3
|View full text |Cite
|
Sign up to set email alerts
|

Favipiravir (T-705) protects against Nipah virus infection in the hamster model

Abstract: Nipah and Hendra viruses are recently emerged bat-borne paramyxoviruses (genus Henipavirus) causing severe encephalitis and respiratory disease in humans with fatality rates ranging from 40–75%. Despite the severe pathogenicity of these viruses and their pandemic potential, no therapeutics or vaccines are currently approved for use in humans. Favipiravir (T-705) is a purine analogue antiviral approved for use in Japan against emerging influenza strains; and several phase 2 and 3 clinical trials are ongoing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
98
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 54 publications
0
98
0
1
Order By: Relevance
“…54 A recent hit on broad-spectrum small molecule antiviral purine analogue previously mentioned Favipiravir (T-705) which inhibits NIV and HeV replication in vitro with a minimal cytotoxic effect of highest concentration tested, having a CC 50 value of N1000 μl (as observed in Hamster model) has provided a way to fight against the cytopathic effect of deadly NiV, HeV like paramyxoviruses. 6 35 It is not late when one day due to the consistent change in their genome these pathogens would get resistance to the conventional drugs which are unidirectional and have no specific targeted. These limitations could be ameliorated by finding a novel therapy with multiple pathways and biomarkers for the target oriented action.…”
Section: Molecular Changes In Detailmentioning
confidence: 99%
See 2 more Smart Citations
“…54 A recent hit on broad-spectrum small molecule antiviral purine analogue previously mentioned Favipiravir (T-705) which inhibits NIV and HeV replication in vitro with a minimal cytotoxic effect of highest concentration tested, having a CC 50 value of N1000 μl (as observed in Hamster model) has provided a way to fight against the cytopathic effect of deadly NiV, HeV like paramyxoviruses. 6 35 It is not late when one day due to the consistent change in their genome these pathogens would get resistance to the conventional drugs which are unidirectional and have no specific targeted. These limitations could be ameliorated by finding a novel therapy with multiple pathways and biomarkers for the target oriented action.…”
Section: Molecular Changes In Detailmentioning
confidence: 99%
“…5 Moreover, the conventional unidirectional serological diagnosis and therapeutics orchestrate numeral shortcomings such as cost deficit, sophisticated preparation procedures, efficient only on postexposure prophylaxis and reduced amount of the product in consistent with human population and livestock to be vaccinated. 5,6 Majority of the therapeutics developed basically includes monoclonal antibodies targeting viral surface proteins such as F, G or M proteins. [7][8][9] Further a number of broad spectrum antiviral agents such as nucleoside analogues namely rebavirin, GS-441524, GS-5734 (remdesivir), R1479 (balapiravir) and most recent drug favipiravir (T-705; 6-flouro-3-hydroxy-2-pyrazinecarboxamine) which is an inhibitor of viral RNA-dependent RNA polymerase have shown certain degree of efficiency against this virus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Singapore outbreak, acyclovir was given to all NiV encephalitis patients and only one death reported due NiV infection, but the role of acyclovir drug is still unclear . In a recent in vivo study, Favipiravir (T‐705) antiviral showed promising results when tested on NiV infected golden hamsters . A study involving use of vaccine against NiV has shown promising results in hamster models .…”
Section: Nipah Virus Outbreaks (1998‐2018)mentioning
confidence: 99%
“…A study involving use of vaccine against NiV has shown promising results in hamster models . As Nipah outbreaks are often associated with high mortality and have great impact on community health, there is a strong need of specific antiviral agents for early treatment of NiV …”
Section: Nipah Virus Outbreaks (1998‐2018)mentioning
confidence: 99%